Desain Media Pembelajaran Kolaboratif “Manfaat Tumbuhan bagi Manusia dan Hewan” Menggunakan Seesaw untuk Pengumpulan Proyek dan Qreatif Educative untuk Materi Interaktif Kelas III Sekolah Dasar (Jurnal Insan Pendidikan dan Sosial Humaniora, 2026)
The development of digital technology requires elementary school teachers to design learning activities that are active, collaborative, and meaningful in accordance with the Merdeka Curriculum. This study aims to describe the design of collaborative learning media on the topic Benefits of Plants for Humans and Animals for third-grade elementary students by utilizing Seesaw as a project collection platform and Qreatif Educative as an interactive learning material media. This study employed a qualitative approach using a literature study method. Data were collected through the review of textbooks, national and international scientific journals, and curriculum documents relevant to the research topic. The results indicate that the integration of Qreatif Educative and Seesaw aligns with constructivist and contextual learning theories. Qreatif Educative supports students’ conceptual understanding through visual and interactive content, while Seesaw facilitates collaborative learning through project submission, reflection, and feedback. This collaborative learning media design has the potential to enhance students’ engagement, collaboration skills, and conceptual understanding in IPAS learning for third-grade elementary school students. Therefore, the use of Seesaw and Qreatif Educative can serve as an alternative digital learning media to support active and meaningful learning in elementary education.